An introduction to the design and fabrication progress of a megawatt class 2G HTS motor for the ship propulsion application. (2nd February 2016) - Moon, Heejong; Kim, Yeong-Chun; Park, Heui-Joo; Yu, In-Keun; Park, Minwon
Abstract: This paper introduces the design and fabrication progress of a megawatt class 2G high temperature superconductor (HTS) motor for the ship propulsion application at Doosan Heavy Industries and Construction. The purpose of this 2G HTS propulsion motor is to launch the business area for marine applications such as surface ship, submarine, merchant ship etc. The principles and interpretation of the magnetic field for 2G HTS motor and permanent magnet type motors are similar on the basis of 3D design and production. The most important component of an HTS motor is the rotor, which is composed of HTS coil, non-ferrous metal, torque disk, damper, and hollow shaft. A HTS rotor using hastelloy-based 2G HTS coils was designed and built. Open-circuit and short-circuit characteristics of the superconducting motor were investigated and compared with the analysis results at reduced excitation to verify the design. Preliminary testing of a 2G HTS motor has been conducted at a few hundred kilowatts as per the design. Through these results, we anticipate that most of the design criteria can be satisfied. However, we have faced several issues during the testing of the motor and these issues need to be resolved in order to take the design further.